Design of Knife Profile and Hopper Position of Banana Chopper Machine - Achmad Arifin; Muhammad Taufik Amri (Program Studi Sarjana Terapan Teknik Mesin, Fakultas Vokasi, Universitas Negeri Yogyakarta, 2025)
Banana chopper machine is a machine used to cut bananas to be processed into banana chips. In its use, banana chopper machines often experience problems in cutting bananas. Obstacles in cutting bananas affect pieces that are damaged or deformed and the size of the pieces is still not wide, and the thickness is still above 2 mm. The aim of this study was to produce banana slices with an elongated oval shape and the slices remained intact with an average thickness of 2 mm. This study used the R&D method and direct trials on banana percussion machines. The collection and presentation of data uses ten samples of banana cutting results with three tests and will measure the thickness of the banana and observe the results of the banana slices visually. The results of this study were in the form of banana slices that were tried on a banana chopper machine and modifications were made to the parts hopper and blade profile. Modification hopper beveled at the ends hopper and the blade profile is made curved